2013
DOI: 10.1002/anie.201304529
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide as a C1 Building Block for the Formation of Carboxylic Acids by Formal Catalytic Hydrocarboxylation

Abstract: A happy marriage of two processes: An effective catalytic system was identified for the direct synthesis of carboxylic acids from non‐activated olefins or alcohols, CO2, and H2. Detailed analysis together with labeling studies indicated that the overall hydrocarboxylation of simple olefins results from a combination of the reverse water–gas shift (rWGS) reaction and a hydroxycarbonylation step, each promoted by a rhodium catalyst (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(116 citation statements)
references
References 43 publications
0
110
0
6
Order By: Relevance
“…These processes make use of the so-called water-gas shift reaction (WGSR) using CO/H 2 O and CO 2 / H 2 pairs [81]. A few number of reductive carboxylation of olefins following a reverse water-gas shift reaction (rWGSR) principle has been achieved, especially in the presence of Rh [82]. Recently, the hydroxycarbonylation of styrenes and aliphatic olefins has been addressed by in situ generation of CO from CO 2 and MeOH, using Ni [83] and Ru catalysts [84].…”
Section: Catalytic Reductive Carboxylation Of Alkenes With Comentioning
confidence: 99%
“…These processes make use of the so-called water-gas shift reaction (WGSR) using CO/H 2 O and CO 2 / H 2 pairs [81]. A few number of reductive carboxylation of olefins following a reverse water-gas shift reaction (rWGSR) principle has been achieved, especially in the presence of Rh [82]. Recently, the hydroxycarbonylation of styrenes and aliphatic olefins has been addressed by in situ generation of CO from CO 2 and MeOH, using Ni [83] and Ru catalysts [84].…”
Section: Catalytic Reductive Carboxylation Of Alkenes With Comentioning
confidence: 99%
“…[16] Ag eneral problem of such reactions is the formation of the corresponding ether from the alcohol. [18] Based on our continuous interest in transition-metalcatalyzed reactions with CO,recently we became attracted to investigate the carbonylation of alcohols in more detail. [17] Moreover,the application of sec-alcohols to give linear esters has not been studied yet.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In spite of the obvious thermodynamic preference of the WGSR (ΔH = −9.8 kcal mol −1 ), 14 this step (even if operational) seemed not to play any crucial role in the process. 18 Very recently, another catalytic protocol for hydrocarboxylation of both linear and cyclic alkenes has been disclosed by Leitner et al; 19 this protocol uses [RhCl(CO) 2 ] 2 /PPh 3 / p-TsOH·H 2 O as precatalysts coupled with CH 3 I as a promoter and H 2 as a hydrogen source/reductant. In seminal contributions, it has been demonstrated that the "direct" carboxylation of ethylene with CO 2 , mediated by homogeneous catalytic systems ((Ph 3 P) 2 PdCl 2 /HCl or (Ph 3 P) 3 RhCl/HBr), required very harsh conditions (120-180°C, 150-700 atm) and resulted in the formation of propionic acid in 38% yield, with ethanol and ethyl propionate as the major byproducts.…”
Section: Some Thermodynamic Considerationsmentioning
confidence: 99%
“…Yet, electrochemical coupling of CO 2 with α-olefins ( propylene and 1-butene) mediated by Ni(II) complexes has been reported to afford mixtures of two major products, namely, a substituted succinic acid and the corresponding unsaturated monocarboxylic acid (Scheme 4). 19 formation of these products remains unclear. The mechanism of Scheme 2 Proposed mechanism for the Pd catalyzed hydroxycarbonylation of olefins with CO/H 2 O (only formation of the linear product is illustrated).…”
Section: Some Thermodynamic Considerationsmentioning
confidence: 99%